1999
DOI: 10.1074/jbc.274.52.37461
|View full text |Cite
|
Sign up to set email alerts
|

Connective Tissue Growth Factor Induces Apoptosis in Human Breast Cancer Cell Line MCF-7

Abstract: Connective tissue growth factor (CTGF) is a member of an emerging CCN gene family that is implicated in various diseases associated with fibro-proliferative disorder including scleroderma and atherosclerosis. The function of CTGF in human cancer is largely unknown. We now show that CTGF induces apoptosis in the human breast cancer cell line MCF-7. CTGF mRNA was completely absent in MCF-7 but strongly induced by treatment with transforming growth factor ␤ (TGF-␤). TGF-␤ by itself induced apoptosis in MCF-7, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
105
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(116 citation statements)
references
References 41 publications
8
105
0
Order By: Relevance
“…In addition, the fact that high levels of CTGF expression is limited to particular types of cells, such as hypertrophic chondrocytes, suggests that expression of the ctgf gene may be under repressed conditions generally in vivo. Otherwise, even apoptosis might be induced by over-expressed CTGF, as reported in a particular cell line (Hishikawa et al, 1999). In concordance with these data, we had previously found that the 3'-untranslated region (3'-UTR) of the CTGF gene exerts repressive e ects on gene expression in cis (Kubota et al, 1999b).…”
Section: Introductionsupporting
confidence: 80%
“…In addition, the fact that high levels of CTGF expression is limited to particular types of cells, such as hypertrophic chondrocytes, suggests that expression of the ctgf gene may be under repressed conditions generally in vivo. Otherwise, even apoptosis might be induced by over-expressed CTGF, as reported in a particular cell line (Hishikawa et al, 1999). In concordance with these data, we had previously found that the 3'-untranslated region (3'-UTR) of the CTGF gene exerts repressive e ects on gene expression in cis (Kubota et al, 1999b).…”
Section: Introductionsupporting
confidence: 80%
“…In addition, breast cancer patients with a poor prognosis and mortality had significantly lower CTFG levels compared with their normal breast tissues (13). Forced expression of CTGF in MCF-7 breast cancer cells increased cell apoptosis (15). In addition, patients with lung adenocarcinoma with low CTGF expression more often had an advanced stage and a poorer prognosis (18).…”
Section: Discussionmentioning
confidence: 99%
“…4A, right). MCF-7 cells were used as control because recombinant CTGF protein has been shown to cause growth inhibition in MCF-7 cells (15). Heparin affinity chromatography has been used in CTGF purification (21).…”
Section: Growth Inhibition Of Nsclc Cells By Ctgf Overexpressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we suggest that in MCF-7 cells another mechanism exists, which is a caspase-3 independent pathway causing the DNA fragmentation observed in this study. Many studies have utilised MCF-7 cells to study apoptosis and have demonstrated DNA fragmentation in response to many stimuli (Saunders et al, 1997;Hishikawa et al, 1999;Tudor et al, 2000). For example, nitric oxide induced apoptosis in MCF-7 cells with a lack of DEVDase activity substantiating the suggestion for an alternative mechanism in MCF-7 and possibly other cells that do not express caspase-3 (Umansky et al, 2000).…”
Section: Effect Of Staurosporine On Bcl-2 Bcl-x L Bak and Bax Proteimentioning
confidence: 99%